EARLY-LIFE ANTIBIOTIC EXPOSURE AND THE RISK OF ATOPIC DERMATITIS IN CHILDREN: A NARRATIVE REVIEW OF GUT MICROBIOTA-RELATED MECHANISMS - Stępień, Gabriela; Przewoźna, Urszula; Szubert, Izabela; Lamorski, Jakub; Suchecka, Julia; Chudecka, Karolina; Józwa, Katarzyna; Chylewski, Michał; Kędzierska, Aleksandra; Nesterak, Wiktor; Łysiak, Jędrzej; Abdulgater, Amin (International Journal of Innovative Technologies in Social Science, 2026)
Background: Atopic dermatitis is one of the most common chronic inflammatory diseases in childhood, and its prevalence has markedly increased in industrialized countries over recent decades. Increasing attention has been directed toward the role of the gut microbiota in immune system development and in the pathogenesis of allergic diseases. Early-life antibiotic exposure is considered one of the major environmental factors capable of disrupting the normal maturation of the intestinal microbiome.Aim: The aim of this literature review was to analyze current evidence regarding the association between prenatal and early childhood antibiotic exposure and the risk of atopic dermatitis in children, with particular emphasis on mechanisms related to gut microbiota dysbiosis and the gut–skin axis.Methods: A narrative literature review was conducted based on currently available cohort studies, observational studies, and meta-analyses investigating the relationship between prenatal and early-life antibiotic exposure, alterations in gut microbiota composition, and the development of atopic dermatitis in children.Results: Available studies indicate that antibiotic therapy during infancy may reduce bacterial diversity, impair short-chain fatty acid production, and dysregulate immune responses mediated by T helper 2 (Th2) lymphocytes. These alterations may contribute to increased intestinal permeability and chronic inflammatory processes involved in the development of atopic dermatitis. Several cohort studies and meta-analyses suggest a positive association between early antibiotic exposure and an elevated risk of atopic dermatitis, although the strength of this relationship varies depending on exposure timing, antibiotic class, outcome definition, and control for confounding factors.Conclusions: Current evidence supports a potential link between prenatal and early childhood antibiotic exposure and an increased risk of atopic dermatitis through mechanisms associated with gut microbiota dysbiosis and the gut–skin axis. However, further prospective studies are required to establish causal relationships more precisely.